Comparison of Microbial Communities in Colorado Potato Beetles (Leptinotarsa decemlineata Say) Collected From Different Sources in China - Yu, Yanxue; Wang, Yuhan; Li, Hongwei; Yu, Xin; Shi, Wangpeng; Zhai, Junfeng (Frontiers in Microbiology, 2021)
Microbial communities in insects are related to their geographical sources and contribute to adaptation to the local habitat. The Colorado potato beetle (Leptinotarsa decemlineata) (CPB) is a potato pest that causes serious economic losses in Xinjiang Uygur Autonomous Region （XJ） and Heilongjiang Province （HL）, China. The influence of microorganisms in the invasion and dispersal of CPB is unclear. We studied microbial communities of CPB collected from nine geographic sources in China using high throughput sequencing technology. Bacteroidetes, Firmicutes, and Proteobacteria were the most dominant phyla, Clostridia, Bacteroidetes, and γ-Proteobacteria were the most dominant classes, Enterobacterales, Lactobacillales, Clostridiales, and Bacteroidales were the most dominant orders, and Enterobacteriaceae, Streptococcidae, Verrucomicrobiaceae, and Rikenellaceae were the most dominant families. There were significant differences, among sources, in the relative abundance of taxa at the genus level. A total of 383 genera were identified, and the dominant bacteria at the genus level were compared between XJ and HL. Pseudomonas was the unique dominant microorganism in the HL area, and the other four microorganisms (Lelliottia, Enterococcus, Enterobacter, and Lactococcus) were common within the 2 regions. Bacterial community diversity in CPB from Urumqi, Jimunai, and Wenquan was higher than diversity in other regions. T-Distributed Stochastic Neighbor Embedding (tSNE) analysis indicated that order and genus were appropriate taxonomic levels to distinguish geographical sources of CPB. These findings provide insight into the roles of microorganisms in the adaptation of CPBs to newly invaded areas.